Pengembangan Backend Platform Konseling Mental Menggunakan Express Js - Muhamad Al Fajri; Misna Asqia (DBESTI: Journal of Digital Business and Technology Innovation, 2026)
This study discusses the development of a backend system for a web-based mental health counseling platform in response to the growing public need for accessible, safe, and user-friendly counseling services. The platform is designed to facilitate interactions between users and psychologists through a structured and efficient digital system. The objective of this study is to develop the backend component to complement the previously built frontend, enabling the platform to function as a complete system for end users. The development process was carried out using the Extreme Programming (XP) method, which emphasizes rapid iteration, team collaboration, and continuous testing. The backend was built using Node.js and Express.js, and follows a REST API architecture to support core features such as user authentication, consultation schedule management, and user-psychologist communication. Testing was conducted using the black box testing method with 53 test scenarios covering the system’s full functionality. The results showed that all implemented features functioned smoothly and produced the expected output. This research concludes that the backend system operates optimally and is ready for integration with the frontend to deliver effective digital counseling services.